Transcriptome Analysis of a Female-sterile Mutant (fsm) in Chinese Cabbage (Brassica campestris ssp. pekinensis) - Huang, Shengnan; Liu, Zhiyong; Li, Chengyu; Yao, Runpeng; Li, Danyang; Hou, Li; Li, Xiang; Liu, Wenjie; Feng, Hui (Frontiers in Plant Science, 2017)
Female-sterile mutants are ideal materials for studying pistil development in plants. Here, we identified a female-sterile mutant fsm in Chinese cabbage. This mutant, which exhibited stable inheritance, was derived from Chinese cabbage DH line ‘FT’ using a combination of isolated microspore culture and ethyl methanesulfonate (EMS) mutagenesis. Compared with the wild-type line ‘FT’, the fsm plants exhibited pistil abortion, and floral organs were also relatively smaller. Genetic analysis indicated that the phenotype of fsm is controlled by a single recessive nuclear gene. Morphological observations revealed that the presence of abnormal ovules in fsm likely influenced normal fertilization process, ultimately leading to female sterility. Comparative transcriptome analysis on the flower buds of ‘FT’ and fsm using RNA-Seq revealed a total of 1,872 differentially expressed genes (DEGs). Of these, a number of genes involved in pistil development were identified, such as PRETTY FEW SEEDS 2 (PFS2), temperature-induced lipocalin (TIL), AGAMOUS-LIKE (AGL) and HECATE (HEC). Furthermore, GO and KEGG pathway enrichment analyses of the DEGs suggested that a variety of biological processes and metabolic pathways are significantly enriched during pistil development. In addition, the expression patterns of 16 DEGs, including four pistil development-related genes and twelve floral organ development-related genes, were analyzed using qRT-PCR. A total of 31,272 single nucleotide polymorphisms (SNPs) were specifically detected in fsm. These results contribute to shed light on the regulatory mechanisms underlying pistil development in Chinese cabbage.